Decision making in root‐coverage procedures for the esthetic outcome. Issue 1 (4th March 2018) - Stefanini, Martina; Marzadori, Matteo; Aroca, Sofia; Felice, Pietro; Sangiorgi, Matteo; Zucchelli, Giovanni
Abstract: The primary indication for treatment of gingival recessions is esthetics. In the last decades, patients have become increasingly more demanding in the esthetic outcome expected. In order to obtain a successful final result, periodontal plastic surgery should provide not only complete root coverage but also perfect blending in terms of color and texture. In the literature, many techniques have been demonstrated to be effective in obtaining complete root coverage, and the selection of one surgical technique over another depends on several factors related to the anatomic characteristics of the defect. The purpose of this paper was to suggest a decision‐making process which starts from the clinical observation of the defects and is structured in progressive nodes that will guide the clinician through the most suitable surgical technique to achieve the ideal esthetic outcome.